Self-Capacity Development of Family Welfare Program Cadres in the E-Commerce Era - Retnowati, Elais; Sutisna, Anan; Warokka, Ari (Journal of Nonformal Education, 2023)
Empowerment and Family Welfare, as an organizational institution, aims to increase the role of the community, one of which is the active role of women. Especially in the PKK organization in Lubang Buaya, which is actively involved in empowering women. In this case, the PKK organization in Lubang Buaya prioritizes increasing women's productivity by creating work programs in various fields. Like the creative econ-omy. Thus, this study aims to explain the role of Empowerment and Family Welfare (PKK) in Lubang Buaya Village, East Jakarta City, in the implementation of empowering women, especially as SMEs in the Creative Economy sector. This study uses a qualitative research approach with a case study research method. Observation, interviews, and documentation carried out the study's data collection process. Using analytical techniques ranging from data reduction and presentation to drawing conclusions. Researchers also use data triangulation techniques for data validity. The results of the research show that there is a role for PKK organizations, such as organizing training programs and MSME bazaar activities to encourage women in Lubang Buaya Village to produce work and start their businesses. Activities for empowering women entrepreneurs of MSMEs are also channeled through social media. Thus, the PKK organization of Lubang Buaya Village is proven to be optimal in accommodating women, and MSME actors, especially in the creative economy.